PERUBAHAN KARAKTERISTIK FISIK FLOK LUMPUR ALUM PADA PENGKONDISIAN GANDA DENGAN POLIMER - Bieby Voijant Tangahu (Purifikasi, 2005)
Several alum sludge properties are high water concentration, resistance to mechanical dewatering and hard to be disposed of or handled. Alum sludge is hard to be dewatered because of its physical characteristics, thus it is often conditioned by using polymer to alter its characteristics, so it is easier to be dewatered. This research was aimed to study amphoteric polymer capability to change physical characteristics of flocs in dual conditioning for alum sludge. Dual conditioning using amphoteric polymer, produced flocs with greater size than single conditioning, also high flocs strength and fractal dimension.